The missing piece: On namespace management in NDN and how DNSsec might help - Pouyan Fotouhi Tehrani; Eric Osterweil; Jochen Schiller; Thomas C. Schmidt; Matthias Wählisch (ACM Conference on Information-Centric Networking 2019, 2019)
Names are the cornerstone of every Information-Centric Network (ICN), nonetheless, name space management has been by far neglected in ICN. A global and scalable name space management is a challenge which not only concerns technical, but also requires attention to non-technical, e.g., judicial, issues. In this short paper, we conceptualize a name space management system for hierarchical names. We present a prototype for NDN, which leverages existing DNSSEC equipped DNS infrastructure. Based on this, we are able to implement both technical and non-technical aspects of name space management. We consider lessons learned and pitfalls from decades of ever-evolving development of domain name system, as de facto standard name space management for the Internet, as an integral orientation factor for both our concept and its implementation.
Keywords: Data origin authentication; DNS; DNSSEC; ICN; Namespace management; NDN